Preparing superhydrophobic nanocomposite coating with SiO2 nanoparticles on magnesium alloy. (3rd October 2021) - Luo, Yufang; Yao, Wenhui; Fu, Wensheng; Wu, Liang; Zhang, Dingfei; Pan, Fusheng
ABSTRACT: Magnesium (Mg) alloys attract a lot of attention owing to their superior properties, while the poor corrosion resistance significantly restricts their extensive applications in practice. The development of a superhydrophobic coating can effectively decrease the contact area between corrosive solutions and the Mg substrate, consequently providing corrosion protection. Herein, a facile approach was proposed, with low cost and no damage to the environment. A nanocomposite coating composed of polyvinylidene fluoride and chemically modified SiO2 nanoparticles was successfully constructed on the Mg alloy by a spraying method. The nanocomposite coating presented irregular structures with accumulated SiO2 nanoparticles, entrapped a lot of air pockets. The water contact angle was up to 151.8°. The corrosion current density was reduced by one order of magnitude compared to that of the bare substrate. Therefore, the nanocomposite coating can provide good corrosion protection for the Mg substrate, accelerating the extensive applications of Mg alloys.